Noise Pollution And Control - Chauhan, Ranjeeta; Butola, Arjun (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Noise is the disturbing or excessive sound that disrupts a personal’s life. It can come from a wide variety of sources, including machines and animals. Now noise pollution, noise control and their principles play a vital role in providing an acoustically pleasing environment. This can be achieved by using various techniques and by using different sound absorbing materials. This research paper helps in overcoming the drawbacks of noise absorbing materials and noise control. Mostly these materials are unsuitable for molding, non-recyclable, difficult to handle and install, accumulate dust and high density of foams. Absorbing materials should be manufactured by natural, biodegradable raw materials. The benefits of these materials are reuse of raw materials and diminishing manufacturing cost. Materials absorb noise and convert it to thermal energy through dissipation. Fibrous, porous or reactive resonators and other materials have been mostly accepted as sound absorptive materials and are generally resistive in nature. The amount of effective absorption is not only dependent on the absorption coefficient, but also the position of absorbent materials in the room and its relation to other surfaces. As a final objective, this research describes how the physical elements of nonwoven sound absorbent system like fiber type, fiber size, fiber cross section, material thickness, density, airflow resistance and porosity can change absorption behavior of nonwovens and noise control.